Сек’юретизація активів як елемент ефективності управління портфелем страхової компанії - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Ільченко, Олександр Олегович; Ilchenko, Oleksandr (Мукачівський державний університет, 2023)
У статті розкриваються принципи сек’юретизації , а також проблема нестачі фінансових ресурсів на сучасному фінансовому ринку в контексті управління портфелем страхової компанії. Виділено переваги сек’юретизації та функціональні особливості інвестиційних учасників і суб’єктів фінансового ринку, які задіяні в процесі сек’юретизації. Узагальнено підходи до визначення класифікаційних ознак за окремими видами активів при їх сек’юретизації. Авторами визначено напрямки вдосконалення механізму процесу залучення грошових коштів і фінансових ресурсів для фінансування страховиків. Також запропоновано способи залучення капіталу з метою інвестування активів страхових компаній у високодохідні інструменти. Проаналізовано диференціацію грошових потоків при підвищенні ефективності інвестування окремих фінансових інструментів страхової організації. The article reveals the principles of securitization, as well as the problem of lack of financial resources in the modern financial market in the context of managing the insurance company's portfolio. Approaches to determining classification features for individual types of assets during their securitization are summarized. The importance of the proposed study is determined by the need to determine ways to improve the securitization of financial assets in Ukraine and its use as a potential factor in strengthening the competitive positions of the Ukrainian financial system. Certain schemes and components of the securitization process have been identified and provided with various structured financial instruments. The authors have determined directions for improving the mechanism of the process of attracting funds and financial resources for financing insurers. Methods of attracting capital with the aim of investing the assets of insurance companies in high-yield instruments are also proposed. The differentiation of cash flows with increasing investment efficiency of individual financial instruments of the insurance organization is analyzed. Securitization of financial assets involves financial institutions obtaining profit from the sale of a pool of financial assets that generate stable cash flows to a specially created legal entity, which subsequently issues securities with new properties and various forms of collateral. This form of innovative investment, such as securitization, will help to solve the problem of shortage of financial resources with the help of the asset financing mechanism, will contribute to increasing the efficiency of portfolio management and the functioning of insurance companies. Also, securitization, like any other financial operations, is also characterized by certain risks, which, first of all, will depend on the specifics of the collateral (securitized assets), the number of participants in the process, and the types of securities. In addition, the correct structuring of securitization relations makes it possible to distribute the risks inherent in assets among the participants of the relations in such a way that each of them is able to objectively assess them and competently minimize them. Risks that arise during securitization are minimized as much as possible by distribution among the main participants of the agreement, due to the use of reliability enhancement mechanisms.
Securitization of assets as an element of the efficiency of portfolio management of an insurance company companies
Keywords: сек’юретизація; securitization; активи; ssets; фінансування; financing; інвестування; investment; страхова компанія; insurance company; ефективність управління; management efficiency